Pengaruh Kebijakan Dividen Terhadap Nilai Perusahaan (Studi Kasus Perusahaan Lq-45) - Reva Yuliani; Vincentia Wahju Widajatun (Jurnal Riset dan Inovasi Manajemen, 2023)
Dividend distribution by companies listed on the Indonesia Stock Exchange is a consideration of investors in making investments. Dividend policy considers how much dividends will be paid, the frequency of dividend payments, and the method of dividend payments, both in cash and in the form of stock dividends. The decisions of these investors affect the price of shares on the stock exchange. The market price of a company's shares formed between buyers and sellers during a transaction is called the company's market value, because the price on the stock exchange is considered a reflection of the real value of the company's assets. The stock price in the market shows the performance of the company. This study shows the relationship between dividend policy and PBV which reflects company performance. By using quantitative research methods. It can be concluded that dividend policy affects PBV..